Comparative iTRAQ-based quantitative proteomic analysis of the Chinese grass shrimp (Palaemonetes sinensis) infected with the isopod parasite Tachaea chinensis - Yingdong Li; Xin Li; Weibin Xu; Zhibin Han; Yingying Zhao; Jing Dong; Hua Wei; Qijun Chen (Parasites & Vectors, 2019)
Abstract Background Although parasitic isopods can negatively affect the reproduction and ingestion of several commercially important crustaceans, little is known regarding the mechanisms that underlie these effects. Methods In the present study, the iTRAQ (isobaric tags for relative and absolute quantification) approach was applied to identify differentially expressed proteins in the Chinese grass shrimp Palaemonetes sinensis infected with the parasitic isopod Tachaea chinensis. Results On the basis of our analysis, we identified 1262 proteins from a total of 4292 peptides. There was a significant difference in the expression of 182 proteins between the control and infected groups, among which 69 were upregulated and 113 were downregulated after T. chinensis infection. The differentially expressed proteins revealed that parasitism may inhibit the immune response, thereby increasing host vulnerability to additional lethal infection. Furthermore, T. chinensis may secrete anticoagulants to inhibit hemolymph clotting. Moreover, the isopod parasite placed a heavy metabolic burden on the host, particularly with respect to glucose metabolism. Conclusions Our study is the first to use the iTRAQ-based proteomic approach to analyze the effects of an isopod parasite on its host. The results we obtained using this approach will make a valuable contribution to understanding the molecular mechanisms underlying isopod parasitism on crustaceans.